Morfología del polen de especies neotropicales de Podostemum(Podostemaceae) - M. Passarelli, Lilian; M. Tur, Nuncia; B. Girarde, Susana (Revista de Biología Tropical, 2010)
Pollen morphology of neotropical species of Podostemum is described for the first time with light (LM) and scanning electronic microscopes (SEM), using pollen dehydration by critical point. Herbarium specimens under study are P. comatum, P. distichum, P. muelleri and P. rutifolium. Pollen grains are dispersed in dyads. Observed with LM, dyads range from 21 to 31μm in lengh and 12 to 18μm wide. individual pollen grains are radially symmetrical spheroidal to subprolate, and have a tricolpate aperture. The exine is tectate, psilate, with an infratectal structure formed by simple columella under the tectum. With SEM, an abundant pollen surface coat is observed all over the pollen grains, mainly in the two grains dyad contact zone. This pollen coat would protect the grains from dehydration because the environments in which these plants grow have important water variation and pollination is not zoophilic. The shared dyad wall shows bridges that partially fusion the exines, forming calymate dyads. Some dyads bear the apertures aligned between grains and some not. The transverse condition of the aperture or aperture in “L” that occurs in the four studied species is described for the first time. it is interpreted as a trend of the genus to espiroaperture. This change in the aperture would be associated with phenology because it is a genus with very short flowering and anthesis, generally a day of anthesis in the dry season. The spiroaperture increases the chances of germination sites and would also have a harmomegata role in an environment with water changes favoring the reproductive success.Walls have a microechinate sculpture, with or without pads at the base of the microechinae. Size of ornamental processes differs, and the colpus membrane has similar ornamentation to that of the non apertural wall, but with larger processes. individual morphology of pollen grains is similar to that described for other family genera as Apinagia and Mourera.During previous stages of anthesis, the presence of cross tetrads was observed, also a new contribution for this genus.